(untitled) (One Health Journal of Nepal, 2021)
Introduction: Malnutrition is a severe public health issue in Nepal. The nutritional status is critical part of health and development among school going children and is the important indices of their quality of life. This study aimed to assess nutritional status of primary school students. Methods: We conducted descriptive cross-sectional study among 301 primary school students of Shiddhicharan municipality. A semi-structured questionnaire was used to assess socio-demographic and behavioral factors. Nutritional assessment was done through anthropometric measurements (height in centimeters and weight in kilograms) using anthropometric tools (weighing machine, height measuring board) and Body Mass Index (BMI) was calculated. The nutritional status of students were classified into underweight, normal, overweight and obese on the basis of Growth Chart (BMI for age) by Center for Disease Control and Prevention criteria. Data were entered and analyzed in Statistical Package for Social Sciences, version 16.0. Results: Of total students, 142 (47.2%) were boys and 159 (52.8%) were girls. The age of the students ranged from 8 years to 16 years with the mean of 12.3士1.7 years. The prevalence of underweight, overweight and obesity among students were 49 (16.3%), 18 (6.0%) and 2 (0.7%) respectively. Malnutrition was slightly concentrated among the boys (26.1%) compared to girls (20.1%). Conclusions: The present study showed the prevailing status of under nutrition with an increasing burden of over nutrition. The current status can be mitigated by increasing awareness in mothers and conducting school health programs focusing on nutrition.